2003
DOI: 10.1189/jlb.0503231
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 transmission and cytokine-induced expression of DC-SIGN in human monocyte-derived macrophages

Abstract: Dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) has been described as an attachment molecule for human immunodeficiency virus type 1 (HIV-1) with the potential to mediate its transmission. We examined DC-SIGN expression in monocyte-derived macrophages (MDM) and its role in viral transmission when MDM were exposed to interleukin (IL)-13, IL-4, or interferon-gamma (IFN-gamma). We show that IL-13 and IL-4 increase transcripts, total protein, and cell-surface expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
48
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 47 publications
11
48
0
Order By: Relevance
“…Our results (Ref. 18 and this report) and those of others (3,4,37) indicate that IL-4 induces DC-SIGN expression on monocytes and monocyte-derived macrophages and is the key cytokine for DC-SIGN acquisition during monocyte-derived dendritic cell differentiation (18). The differential expression of DC-SIGN in differentiated THP-1 in the absence (DC-SIGN dull ) or presence of IL-4 (DC-SIGN high ) further illustrates the impact of IL-4 on myeloid cell differentiation and demonstrates the IL-4 dependence of the DC-SIGN expression in both normal and transformed myeloid cells.…”
Section: Fig 5 Dc-sign-dependent Functions Exhibited By Bryostatin supporting
confidence: 72%
“…Our results (Ref. 18 and this report) and those of others (3,4,37) indicate that IL-4 induces DC-SIGN expression on monocytes and monocyte-derived macrophages and is the key cytokine for DC-SIGN acquisition during monocyte-derived dendritic cell differentiation (18). The differential expression of DC-SIGN in differentiated THP-1 in the absence (DC-SIGN dull ) or presence of IL-4 (DC-SIGN high ) further illustrates the impact of IL-4 on myeloid cell differentiation and demonstrates the IL-4 dependence of the DC-SIGN expression in both normal and transformed myeloid cells.…”
Section: Fig 5 Dc-sign-dependent Functions Exhibited By Bryostatin supporting
confidence: 72%
“…It is possible that the equivalent of the cultured monocyte-derived DCs only develops under select circumstances, e.g., during an inflammatory response or in special tissue niches. We and others (19,31,37,39) found that cytokines such as IL-4, IL-13, and IL-15 quickly up-regulated DC-SIGN expression on monocytes, so that cells with the phenotype of monocyte-derived DCs might accumulate in situations such as parasite infection and allergy. The reports of DC-SIGN Ï© cells in lymphatic sinuses, particularly in the subcapsular region of lymph nodes, may also reflect migratory monocyte-derived DCs responding to a stimulus in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…DC-SIGN is a CLR described in the binding and transmission of human immunodeficiency virus type 1 (5,11) and mediates cell responses via downstream kinase signaling (4). Consistent with an earlier report (4), we found that Lyn, an Src family kinase, was recruited after DC-SIGN ligated with the glycosylated WNV-E protein and that ligation of DC-SIGN increased the phosphorylation of Lyn at the carboxyl terminus, while the phosphorylation at the activation loop of Lyn was unaffected.…”
Section: Discussionmentioning
confidence: 99%